B-cell clusters at the invasive margin associate with longer survival in early-stage oral-tongue cancer patients. (1st January 2021) - Phanthunane, C.; Wijers, R.; de Herdt, M.; Langeveld, T.P.M.; Koljenovic, S.; Dasgupta, S.; Sleijfer, S.; Baatenburg de Jong, R. J.; Hardillo, J.; Balcioglu, H. E.; Debets, R.
ABSTRACT: In oral-cancer, the number of tumor-infiltrating lymphocytes (TILs) associates with improved survival, yet the prognostic value of the cellular composition and localization of TILs is not defined. We quantified densities, localizations, and cellular networks of lymphocyte populations in 138 patients with T1-T2 primary oral-tongue squamous cell carcinoma treated with surgical resections without any perioperative (chemo)radiotherapy, and correlated outcomes to overall survival (OS). Multiplexed in-situ immunofluorescence was performed for DAPI, CD4, CD8, CD20, and pan-cytokeratin using formalin-fixed paraffin-embedded sections, and spatial distributions of lymphocyte populations were assessed in the tumor and stroma compartments at the invasive margin (IM) as well as the center of tumors. We observed a high density of CD4, CD8, and CD20 cells in the stroma compartment at the IM, but neither lymphocyte densities nor networks as single parameters associated with OS. In contrast, assessment of two contextual parameters within the stroma IM region of tumors, i.e., the number of CD20 cells within 20 µm radii of CD20 and CD4 cells, termed the CD20 Cluster Score, yielded a highly significant association with OS (HR 0.38; p = .003). Notably, the CD20 Cluster Score significantly correlated with better OS and disease-free survival in multivariate analysis (HR 0.34 and 0.47; p = .001 and 0.019) as well as with lower local recurrence rate (OR: 0.13; p = .028). Taken together, our study showed that the presence of stromal B-cell clusters at IM, in the co-presence of CD4 T-cells, associates with good prognosis in early oral-tongue cancer patients.